Authoritarian-Benevolent Leadership, Moral Disengagement, and Follower Unethical Pro-organizational Behavior: An Investigation of the Effects of Ambidextrous Leadership - Shaw, Kang-Hwa; Tang, Na; Liao, Hung-Yi (Frontiers in Psychology, 2020)
Drawing on the social cognitive theory of moral disengagement, this study examined the influence of the authoritarian-benevolent style of ambidextrous leadership on follower unethical pro-organizational behavior (UPB), mediated via moral disengagement. We tested the hypotheses using a sample of 175 participants at two time points. The results indicated that authoritarian-benevolent leadership affects moral disengagement. In addition, followers in congruent dyads with low authoritarian-benevolent leadership perceived higher levels of moral disengagement than those in congruent dyads with high authoritarian-benevolent leadership. Furthermore, high authoritarian-benevolent leadership had an indirect effect on follower UPB via moral disengagement. Theoretical and practical implications and future research directions are suggested.